Odpowiedzi

2010-04-14T15:54:18+02:00
X-pierwsza liczba
x+3-druga liczba
x+3+4-trzecia liczba
2/5(x+3)
x+x+3+x+3+4+2/5*(x+3)=35
3x+10+2/5x+6/5=35
3 i 2/5x+11 i 1/5x=35/-11 i 1/5
3 i 2/5x=23 4/5 /:3 i 2/5
x=119/5 razy 5/17
x=119/17=7- pierwsza liczba
7+3=10 druga liczba
7+3+4=14-trzecia liczba
2/5 razy 10=4-czwarta liczba
2010-04-14T15:56:12+02:00
I liczba - x
II liczba - x+3
III liczba - x+3+4 = x+7
IV liczba - 2/5(x+3) = 0,4x+1,2

x+x+3+x+7+0,4x+1,2 = 35
3,4x+11,2 = 35
3,4x = 35-11,2
3,4x = 23,8 |:3,4
x = 7

I liczba - 7
II liczba - 7+3 = 10
III liczba - 7+3+4 = 14
IV liczba - 0,4*7+1,2 = 2,8+1,2 = 4
2010-04-14T15:56:25+02:00
35 = x+ (x+3)+(x+3)* 2/5 +( x+3)+ 4
35= x + x+3+ 2/5x + 6/5 + x +3 +4
35 -3 -6/5 -3 -4 = x + x + 2/5x +x
35 - 10 6/5 = 3 2/5x
35 - 11 1/5 = 3 2/5x
23 4/5 = 3 2/5x

x
(x+3)
(x+3)* 2/5
( x+3)+ 4

itd..